2005
DOI: 10.1073/pnas.0508186102
|View full text |Cite
|
Sign up to set email alerts
|

CHR11, a chromatin-remodeling factor essential for nuclear proliferation during female gametogenesis in Arabidopsis thaliana

Abstract: Chromatin-remodeling factors regulate the establishment of transcriptional programs during plant development. Although 42 genes encoding members of the SWI2͞SNF2 family have been identified in Arabidopsis thaliana, <10 have been assigned a precise function on the basis of a mutant phenotype, and none have been shown to play a specific role during the gametophytic phase of the plant life cycle. A. thaliana chromatin-remodeling protein 11 (CHR11) encodes an imitation of switch (ISWI)-like chromatin-remodeling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 49 publications
(46 reference statements)
1
66
0
1
Order By: Relevance
“…Female gametophyte synergid-, antipodal-, and central cell-specific markers (Huanca-Mamani et al, 2005;Groß-Hardt et al, 2007;Olmedo-Monfil et al, 2010;Tucker et al, 2012) were used to confirm the rpl27ac-2 ovule phenotype. In maturing ovules, GUS expression from the synergid cell marker enhancer trap ET2634 and antipodal cell marker gene trap GT3733 was initially detected in the majority of wild-type and mutant ovules (Fig.…”
Section: The Dose Of Rpl27a Determines the Severity Of Leaf And Ovulementioning
confidence: 99%
See 1 more Smart Citation
“…Female gametophyte synergid-, antipodal-, and central cell-specific markers (Huanca-Mamani et al, 2005;Groß-Hardt et al, 2007;Olmedo-Monfil et al, 2010;Tucker et al, 2012) were used to confirm the rpl27ac-2 ovule phenotype. In maturing ovules, GUS expression from the synergid cell marker enhancer trap ET2634 and antipodal cell marker gene trap GT3733 was initially detected in the majority of wild-type and mutant ovules (Fig.…”
Section: The Dose Of Rpl27a Determines the Severity Of Leaf And Ovulementioning
confidence: 99%
“…rpl27ac-1d carrying RPL27aC:rpl27ac-1d was generated by crossing with RPL27aC:rpl27ac-1d in the wild type to the heterozygous mutant. ET2634, GT3733, pMEA:GUS, pFM2:GUS, and AT1g21670:nls-vYFP were as previously reported (Huanca-Mamani et al, 2005;Groß-Hardt et al, 2007;Olmedo-Monfil et al, 2010;Tucker et al, 2012). rpl27ac-2, rpl27ac-3, rpl27ab-1, rpl27ab-2, and rpl5a-2 in the Col-0 background were backcrossed four to five times to Ler, and unless otherwise stated, these alleles in the Ler background were used in analyses.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Moreover, it has been shown that female gametophytes carrying defective alleles for POLII arrest early in development due to the failure of female megaspores to complete the three rounds of mitosis required for the development of mature gametophytes (Onodera et al, 2008). Using the pFM1 promoter (Huanca-Mamani et al, 2005), which is specifically expressed in the functional megaspore, we saw that transgenic lines with an RNAi construct targeting POLII resulted in immediate developmental arrest at the functional megaspore stage (see Supplemental Figure 1A and Supplemental Table 1 online), thus showing that RNAi against POLII is an efficient way to avert transcription. Another question, however, was whether the RNAi machinery is functional in the seed at early stages.…”
Section: Embryo and Endosperm Have Different Transcriptional Requiremmentioning
confidence: 99%
“…Insertional mutations in NOMEGA (Kwee and Sundaresan, 2003) and ANAPHASE PROMOTING-COMPLEX 2 (APC2) (Capron et al, 2003), encoding two different components of the E3 ligase anaphase promoting complex/cyclosome (APC/C) involved in cell cycle progression, result in the arrest of female gametogenesis after the first nuclear division. Disruption of PROLIFERA (PRL), encoding a Mcm7-like licensing factor essential for DNA replication (Springer et al, 1995), and targeted degradation of the CHROMATIN-REMODELING PROTEIN 11 (CHR11) transcripts through RNA interference (Huanca-Mamani et al 2005) also cause a premature arrest in nuclear division. In the slow walker 1 (swa1) mutant, which is disrupted in a gene encoding a component of the large nucleolar U3 complex required for 18S ribosomal RNA biogenesis, nuclear proliferation in the embryo sac is delayed and asynchronized (Shi et al, 2005).…”
Section: The Midasin and Notchless Genes Are Essential For Female Gammentioning
confidence: 99%